2015
DOI: 10.4253/wjge.v7.i2.110
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band imaging with magnifying endoscopy for the evaluation of gastrointestinal lesions

Abstract: Narrow band imaging (NBI) endoscopy is an optical image enhancing technology that allows a detailed inspection of vascular and mucosal patterns, providing the ability to predict histology during real-time endoscopy. By combining NBI with magnification endoscopy (NBI-ME), the accurate assessment of lesions in the gastrointestinal tract can be achieved, as well as the early detection of neoplasia by emphasizing neovascularization. Promising results of the method in the diagnosis of premalignant and malignant les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Recently, the usefulness of magnifying endoscopy in detecting gastrointestinal lesions has been given attention [39] , and magnifying endoscopy with narrowband imaging (MNBI) is proposed to be a useful technique to diagnose gastric MALT lymphomas [32,40,41] . Interestingly, Nonaka et al [41] reported that MNBI was useful in not only detecting gastric MALT lymphomas but also in evaluating their response to eradication therapy.…”
Section: Table 2 Previous Reports On Helicobacter Pylori -Negative Gamentioning
confidence: 99%
“…Recently, the usefulness of magnifying endoscopy in detecting gastrointestinal lesions has been given attention [39] , and magnifying endoscopy with narrowband imaging (MNBI) is proposed to be a useful technique to diagnose gastric MALT lymphomas [32,40,41] . Interestingly, Nonaka et al [41] reported that MNBI was useful in not only detecting gastric MALT lymphomas but also in evaluating their response to eradication therapy.…”
Section: Table 2 Previous Reports On Helicobacter Pylori -Negative Gamentioning
confidence: 99%
“…On the other hand, in neoplastic lesions the abnormal mucosal and capillary patterns have characteristic features. In squamous neoplastic lesions, IPCLs exhibit characteristic morphological changes, being dilated, tortuous, and irregular in dysplastic lesions, and destructed and replaced by tumor vessels in squamous cell carcinomas (SCCs) [1, 10, 11]. Likewise, in BE a circular and “ridged/villous” pattern with regular vessels is predictive of specialized intestinal metaplasia, and irregular mucosal and vessel patterns are predictive of dysplasia [1, 9].…”
Section: Esophagusmentioning
confidence: 99%
“…Magnification endoscopy with NBI (ME-NBI) also allows a better visualization of normal capillary mucosal vessels (intraepithelial papillary capillary loops [IPCLs]) and submucosal vascularity (branching vessels) [1, 10]. Normal IPCLs are observed as brown loops originating from a branching vessel, running perpendicularly in the lamina propria and finally reaching the intraepithelial papillae (Fig.…”
Section: Esophagusmentioning
confidence: 99%
“…The data from five case-control studies and two cohort studies in Japan demonstrated that photofluoroscopy for gastric cancer screening can decrease gastric cancer mortality by 40-60% [12]. By now, many new advanced approaches providing better visualization of gastric mucosa lesions have been developed, such as chromoendoscopy [62], confocal laser endomicroscopy [63], narrow-band imaging endoscopy [64], magnifying endoscopy [65] and narrow-band imaging with magnifying endoscopy [66]. A large number of studies showed that these new advanced endoscopic imaging technologies have better accuracy for diagnosing premalignant gastric lesions than standard ‘white light' endoscopy [67,68,69].…”
Section: Prevention Strategies For Gastric Cancermentioning
confidence: 99%